Foreign body a fish in orohypopharynx with complication vocal cord paralysis - Ade Asyari; Novialdi Novialdi; Nur Azizah (Faculty of Medicine, Universitas Andalas, 2018)
Introduction: Foreign body a fish in oro-hypopharynx is a rare case and require rapid diagnosis and immediate treatment to prevent complication. There are some complications that can occur, such as upper airway obstruction, perforation of the pharyngeal wall, vocal cord paralysis, pneumomediastinum, and emphysema. Vocal cord paralysis is rare complication caused by a foreign body in the pharynx. The management for pharyngeal foreign bodies is the extraction of a foreign body with Magill forceps, direct laryngoscopy, and rigid endoscopy. Tracheostomy should be performed if endotracheal intubation could not be done or failed to be performed. Objective: Understanding diagnosis and management of patient foreign body a fish in an oro-hypopharynx. Case report: Reported a case, male 40 years old, with diagnosis foreign body a fish in oro-hypopharynx with complication unilateral vocal cord paralysis. The Foreign body was extracted using Magill forceps and rigid esophagoscopy with tracheostomy preparation if endotracheal intubation was failed to perform. Conclusion: Foreign body a fish in oro-hypopharynx is a rare case. Precise diagnosis and treatment are very important to prevent complication. Vocal cord paralysis is a rare complication caused by a foreign body in oro-hypopharynx.